Impact of Political Setups on Foreign Direct Investment in Pakistan - Asif, Muhammad Farhan; Ali, Shafaqat; Khan, Majid; Afridi, Jawad Rahim; Safdar, Hina (The journal of contemporary issues in business and government, 2020)
This paper analyses the impact of different political setups on foreign direct investment (FDI) in Pakistan and examines whether different political setups has any effect on FDI. The time series data from the period 1971-2018 is used. Ordinary least square regression model is run to check the significance of the data and relationship between dependent and independent variables. Gross domestic product, gross capital formation, inflation rate, indirect taxes, exchange rate, trade openness and dummy variable for dictatorship or autocratic regime in Pakistan are taken as an independent variables and FDI as dependent variable. The results of study indicate that in the long run GDP is the major determinant of FDI in Pakistan and is followed by gross capital formation or domestic investment and inflation. The results also indicate that during dictatorship or imperialistic regimes there are less FDI into Pakistan.